The fluid mechanics of ureteroscope irrigation - Williams, J; Turney, B; Rauniyar, N; Harrah, T; Waters, S; Moulton, D (Mary Ann Liebert, 2018)
Purpose To develop a physical understanding of uretero-renoscopy irrigation, we derive mathematical models from basic physical principals, and compare these predictions with the results of bench-top experiments. Mathematical modelling can be used to understand the role of inlet pressure, tip deflection, the presence of working tools, geometric properties of the instruments used, and material properties of the irrigation fluid on resulting flow rate. Materials and Methods We develop theoretical models to describe irrigation flow in an idealised setup and compare with bench-top experiments for flow through a straight scope, a scope with a deflected tip, and a scope with a working tool inserted. The bench-top experiments were performed using Boston Scientific’s LithoVue ureteroscope and a variety of Boston Scientific working tools. Standard ureteroscope working channels have circular cross-sections, but using theoretical models we investigate whether modifications to the cross-sectional geometry can enhance flow rates. Results The theoretical flow predictions are confirmed by experimental results. Tip deflection is shown to have a negligible effect on flow rate, but the presence of working tools decreases flow significantly (for a fixed driving pressure). Flow rate is predicted to improve when tools are placed at the edge of the channel, rather than the center, and modifying the cross-sectional shape from a circle to an ellipse can further increase flow rate. Conclusions A mathematical framework is formulated and shown to accurately predict the properties of ureteroscope irrigation flow. The theoretical approach has significant potential in quantifying irrigation flow and improving ureteroscope design.